Ontological Theology in Religious Zionism—Rabbi Y.M. Harlap as a Case Study - Mashiaḥ, Amir (Religions, 2020)
The present study sets out to shed light on R. Yaakov Moshe Harlap (1882-1951), Kabbalist, head of the Merkaz Ha-Rav yeshivah, in his understanding of ontological theology—material labor, meaning the basic life pattern, in which one gets up daily in the morning and goes to “work.” Did R. Harlap see labor as no more than a need and an obligation incumbent upon man to provide for his family? Or did he, perhaps, see labor as a religious value, an outgrowth of the theology he upheld? The conclusion is that work in the teaching of R. Harlap is not only needed to earn a living, but part of the multidimensional theology of Torah, textual-spiritual study and practical work effort. All this is part of the perfecting of the Land of Israel, which became central in the messianic age. Labor is a precondition and an indication of redemption—national, human and Divine.